Uneven Ground: Nationalist Frames and the Variable Salience of Homeland. (3rd July 2018) - Zellman, Ariel
ABSTRACT: When are domestic publics most sympathetic to nationalist territorial ambitions? Conflict scholars commonly assume support should be greatest when territory is framed as being of intangible value to national identity over tangible importance to national security and economic prosperity. This should be especially true regarding lost homelands, territories wherein a state has previously exercised sovereignty and to which it has enduring ethnic ties. This article presents experimental evidence that directly challenges these assumptions, demonstrating the variability of Serbian popular attachments to three lost territories: Kosovo, Bosnia, and Montenegro. It finds that intangible framings do not necessarily engender stronger assertions that such territories belong to the homeland than tangible framings do. Nor do they necessarily motivate greater support for nationalist territorial agendas. These findings cast doubt on conventional wisdom regarding domestic publics' contributions to territorial conflict and offer refined insights regarding in which instances intangible claims are most conflict-prone.